The Relationship Between Proteinuria Degree of Pre-eclampsia Mother and Incidence of Neonatal Low Birth Weight at General Hospital Karsa Husada Batu - Yuwan Ihzudin Sumitro; Alifia Putri Febriyanti; Prida Ayudianti; Putri Wulan Akbar; Nurfianti Indriana (Journal of Agromedicine and Medical Sciences, 2023)
Preeclampsia is hypertension that occurs after 20 weeks of gestation with proteinuria. As one of the second highest causes of maternal death in Indonesia, preeclampsia must be detected and managed quickly and appropriately before complications that threaten the mother and fetus arise. One of the conditions that can be associated with preeclampsia is the outcome of low birth weight babies (LBW). This study aimed to determine the relationship between the degree of proteinuria in preeclampsia mothers and incidence of LBW at RSU Karsa Husada Batu. This study used a cross-sectional study design. Data was collected from medical record. The independent variable in this study was the degree of proteinuria and the dependent variable was diagnosis of LBW. The population in this study were all preeclampsia mothers and their babies from preeclampsia patients at RSU Karsa Husada Batu in 2021 with total of 38 patient. Sampling was done by total population sampling. Data analysis used in the study is chi square test. The results of this study showed that there is a relationship between the degree of proteinuria in preeclampsia mothers and incidence of LBW or the higher the degree of proteinuria, the higher the risk of babies from preeclampsia patients experiencing LBW ( p=0,005 ; CI = 95%). Keywords: Preeclampsia, Proteinuria, LBW